2018
DOI: 10.1017/s0950268818002467
|View full text |Cite
|
Sign up to set email alerts
|

Detection of East/Central/South African genotype Chikungunya virus during an outbreak in a southeastern state of Brazil

Abstract: Chikungunya virus (CHIKV) is an arbovirus transmitted by Aedes mosquitoes that was first identified in Brazil in 2014. It causes a febrile illness characterised by severe arthralgia and rash. Our group investigated a suspected CHIKV outbreak in Governador Valadares, state of Minas Gerais, Brazil and from 25 acute-phase patients, 10 had qRT-PCR positive sera samples and had E1 partial sequence amplified and Sanger sequenced. Samples were identified as East/Central/South African (ECSA) genotype by phylogenetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
2
4
0
3
Order By: Relevance
“…aegypti was first documented with natural infection by CHIKV in 2017 in Brazil and the Americas, attributed to the ECSA genotype [5], the same found in the present study. This finding aligns with the widespread prevalence of the ECSA genotype since its introduction in 2014 [45], frequently detected in humans CHIK cases in Brazil [46,47], included those in the state of Minas Gerais [48]. Despite its importance, there are few reports on genomic CHIKV surveillance in mosquitoes from Brazil [6,[12][13][14][49][50][51][52].…”
Section: Discussionsupporting
confidence: 66%
“…aegypti was first documented with natural infection by CHIKV in 2017 in Brazil and the Americas, attributed to the ECSA genotype [5], the same found in the present study. This finding aligns with the widespread prevalence of the ECSA genotype since its introduction in 2014 [45], frequently detected in humans CHIK cases in Brazil [46,47], included those in the state of Minas Gerais [48]. Despite its importance, there are few reports on genomic CHIKV surveillance in mosquitoes from Brazil [6,[12][13][14][49][50][51][52].…”
Section: Discussionsupporting
confidence: 66%
“…The CHIKV ECSA genotype was first reported in Brazil in 2014, in Feira de Santana, Bahia, in the Northeast region and, in the following years, spread to other states, being identified in Bahia (2014–2017) [ 9 , 48 , 49 ], Alagoas (2016) [ 46 , 50 ], Piauí (2016–2017) [ 51 ], Sergipe (2016) [ 38 ], and Maranhão (2017) [ 40 ]. It was also identified in the Southeast region, in Rio de Janeiro (2016–2018) [ 52 , 53 ] and Minas Gerais (2017) [ 54 ]. Moreover, it has been suggested that the probable introduction of the ECSA genotype in the North occurred from the Northeast in mid-2015 [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…aegypti in Brazil are restricted to few groups. The available data about CHIKV circulation are obtained from the human cases that show, until now, the circulation of the Asian genotype, in the Northern (state of Amapá [15]) and Southeast (Rio de Janeiro [91,92]) regions, and the ECSA genotype, reported in the Northern (Amazônia [93]), Northeast (Alagoas [88,89], Bahia [15,88,90], Paraíba [88], and Sergipe [90]), and Southeast (in Rio de Janeiro [90,94] and Minas Gerais [95]).…”
Section: Discussionmentioning
confidence: 99%